Post-traumatic deformity of mandibular condyle: descriptive review and proposal of treatment algorithm - Nilesh, Kumar; Vande, Aaditee (Journal of Stomatology, 2020)
Condyle, along with the glenoid fossa and its associated soft tissue components and muscles of mastication, perform various important functions such as mastication, speech, and swallowing. Condyle also act as growth center in child. Hence, any defect in the anatomical form of mandibular condyle affects both the appearance and function. Deformity of mandibular condyle can be acquired due to several reasons. Post-traumatic deformity is a common cause, second to ankylosis. These deformities result due to lack of treatment or inadequate management of condylar fracture. It affects both form and function of lower jaw, compromising facial appearance and occlusion. Many options have been proposed for its treatment, ranging from conservative management to surgical intervention. Conservative management options described in literature include physiotherapy, forceful jaw opening, occlusal grinding, tooth extraction, prosthetic rehabilitation, and orthodontic correction. Surgical management involve condylectomy, orthognathic surgery, autogenous grafts, and prosthetic joint replacement. However, the choice of appropriate treatment depends on variables such as age of patient, timing of intervention, and degree of deformity. There is lack of literature reviewing multiple treatment options for post-traumatic deformity of mandibular condyle. This paper presents a descriptive review of various options for management of post-traumatic deformity of condyle. Treatment algorithm for its management is also presented.